Lifting the lid, 1 - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Here s a tiny preview of how you use Spore from Mr Y Simplice Agbekponou, a veterinarian in Atakpamé, Togo. 'One recent example of what Spore has helped me do is that I cured one hundred chickens of internal parasites by feeding them pawpaw seeds,...